Phylogenomic and comparative genomic studies robustly demarcate two distinct clades of Pseudomonas aeruginosa strains: proposal to transfer the strains from an outlier clade to a novel species Pseudomonas paraeruginosa sp. nov. Issue 11 (9th November 2022) - Rudra, Bashudev; Duncan, Louise; Shah, Ajit J.; Shah, Haroun N.; Gupta, Radhey S.
Abstract : The strains of Pseudomonas aeruginosa exhibit considerable differences in their genotypic and pathogenic properties. To clarify their evolutionary/taxonomic relationships, comprehensive phylogenomic and comparative genomic studies were conducted on the genome sequences of 212 P . aeruginosa strains covering their genetic diversity. In a phylogenomic tree based on 118 conserved proteins, the analysed strains formed two distinct clades. One of these clades, Clade-1, encompassing >70 % of the strains including the type strain DSM 50071 T, represents the species P. aeruginosa sensu stricto . Clade-2, referred to in earlier work as the outlier group, with NCTC 13628 T as its type strain, constitutes a novel species level lineage. The average nucleotide identity, average amino acid identity and digital DNA–DNA hybridization values between the strains from Clade-1 and Clade-2 are in the range of 93.4–93.7, 95.1–95.3 and 52–53 %, respectively. The 16S rRNA gene of P. aeruginosa DSM 50071 T also shows 98.3 % similarity to that of NCTC 13628 T . These values are lower than the suggested cut-off values for species distinction, indicating that the Clade-2 strains (NCTC 13628 T ) constitute a new species. We also report the identification of 12 conserved signature indels in different proteins and 24 conserved signature proteins that are exclusively found in either Clade-1 or Clade-2, providing a reliable means for distinguishing these clades. Additionally, in contrast to swimming motility, twitching motility is only present in Clade-1 strains. Based on earlier work, the strains from these two clades also differ in their pathogenic mechanisms (presence/absence of Type III secretion system), production of biosurfactants, phenazines and siderophores, and several other genomic characteristics. Based on the evidence from different studies, we propose that the Clade-2 strains constitute a novel species for which the name Pseudomonas paraeruginosa is proposed. The type strain is NCTC 13628 T (=PA7 T =ATCC 9027 T ). The description of Pseudomonas aeruginosa is also emended to include information for different molecular markers specific for this species.